Analisis Lingkungan Bisnis dan Harga Jual terhadap Minat Pengusaha Budidaya Sarang Burung Walet di Kelurahan Beriwit Kecamatan Murung Kabupaten Murung Raya Kalimantan Tengah - Salmiyah Salmiyah; Emy Rahmawati; Siti Rusidah (JURNAL BISNIS DAN PEMBANGUNAN, 2019)
Beriwit village is one of the few villages in Murung raya district which swallow nest population is very abundant. This study aims to determine and analyze the environment and selling price to the interests of swallow entrepreneurs in Beriwit Village.The results of this study show that, SWOT matrix and quadrant shows the right strategy is to use SO strategy. If it is further elaborated, it can be obtained that the SO strategy produces several strategies that can be implemented to increase the productivity of the wallet nest so that entrepreneurs can optimize their profits in the future.The conclusion from the research is that the cultivation of swallow nest in the area of Beriwit village is a very profitable business with a significant average production rate increase and the income obtained is fairly stable in 2015 until the year 2018. Keywords: Environment, Selling Price, Interest.